A state-of-the-art review on rock seepage mechanism of water inrush disaster in coal mines - Ma, Dan; Duan, Hongyu; Zhang, Jixiong; Bai, Haibo (International journal of coal science & technology, 2022)
Water inrush is one of the most dangerous disasters in coal mining. Due to the large-scale mining and complicated hydrogeological conditions, thousands of deaths and huge economic losses have been caused by water inrush disasters in China. There are two main factors determining the occurrence of water inrush: water source and water-conducting pathway. Research on the formation mechanism of the water-conducting pathway is the main direction to prevent and control the water inrush, and the seepage mechanism of rock mass during the formation of the water-conducting pathway is the key for the research on the water inrush mechanism. This paper provides a state-of-the-art review of seepage mechanisms during water inrush from three aspects, i.e., mechanisms of stress-seepage coupling, flow regime transformation and rock erosion. Through numerical methods and experimental analysis, the evolution law of stress and seepage fields in the process of water inrush is fully studied; the fluid movement characteristics under different flow regimes are clearly summarized; the law of particle initiation and migration in the process of water inrush is explored, and the effect of rock erosion on hydraulic and mechanical properties of the rock media is also studied. Finally, some limitations of current research are analyzed, and the suggestions for future research on water inrush are proposed in this review.